Assessing the role of health behaviors, socioeconomic status, and cumulative stress for racial/ethnic disparities in obesity - Cuevas, Adolfo G. (Obesity (Silver Spring), 2020)
OBJECTIVE: To examine the explanatory role of health behaviors, socioeconomic position (SEP), and psychosocial stressors on racial/ethnic obesity disparities in a multiethnic and multiracial sample of adults. METHODS: Using data from the Chicago Community Adult Health Study (2001–2003), we conducted Oaxaca-Blinder decomposition analysis to quantify the extent to which health behaviors (fruit and vegetable consumption and physical activity), SEP, and cumulative stressors (e.g., perceived discrimination, financial strain) each explained differences in obesity prevalence in Blacks, US-born Hispanics, and non-US-born Hispanics compared to non-Hispanic Whites. RESULTS: SEP and health behaviors did not explain obesity differences between racial/ethnic minorities and Whites. Having high-level of stress in four or more domains explained 4.46% of the differences between Blacks and Whites, whereas having high-level of stress in three domains significantly explained 14.13% of differences between US-born Hispanics and Whites. Together, the predictors explained less than 20% of differences between any racial/ethnic minority group and Whites. CONCLUSIONS: Exposure to stressors may play a role in obesity disparities, particularly among Blacks and US-born Hispanics. Other obesity-related risk factors need to be examined to understand the underlying mechanisms explaining obesity disparities.